Factors influencing public participation in planning the development of the Mae Lamao Subdistrict Administrative Organization, Mae Sot District, Tak Province - Chumphong, Sunimit; Traisorakunkul, Niphon; Rukliang, Namo; Rojanaprapa, Weeranat; Kaewchoi, Krittiyaphorn (Journal of Dhamma for Life, 2025)
This research study has a purpose to study the level of public participation in planning. Develop the Dan Mae Lamao Subdistrict Administrative Organization, Mae Sot District, Tak Province, to study factors influencing participation. of the people in planning the development of the Dan Mae Lamao Subdistrict Administrative Organization, Mae Sot District, Tak Province and to study Suggestions regarding factors influencing public participation in the development planning of the Dan Mae Lamao Subdistrict Administrative Organization, Mae Sot District, Tak Province, a sample group of 381 people, using Taro Yamane's formula, tools used. In research, these include rating scale questionnaires. Statistics used in data analysis include percentage, mean, frequency, and standard deviation. and multiple regression analysis The results of the research found that (1) the level of public participation in planning the development of the Dan Mae Lamao Subdistrict Administrative Organization, Mae Sot District, Tak Province was overall at a high level. (2) Factors that influence public participation in planning the development of the Dan Mae Lamao Subdistrict Administrative Organization, Mae Sot District, Tak Province, including information perception factors. Community leadership factors Utility factors received Factors of promotion from the government and factors of feeling of belonging to the community. The multiple correlation coefficient was .621, able to jointly explain 62.10% of the variation, with statistical significance at the .05 level. and (3) recommendations that the Dan Mae Lamao Subdistrict Administrative Organization should increase public relations with local people in order to create awareness. News and public participation People should voluntarily participate in volunteer activities and participate in public forums organized by the Subdistrict Administrative Organization. People should work together to protect the interests of their villages. Together they suggest problems or needs for developing their own community to the Subdistrict Administrative Organization. Community leaders should coordinate with the Subdistrict Administrative Organization to create participation or encourage people in the village to be interested. Information on the operations of the Dan Mae Lamao Subdistrict Administrative Organization. Should be publicized in the planning campaign. continuously and coordinate with community leaders to make announcements along the lines.